Pathogenetic and Prognostic Factors for Neonatal Gastric Perforation: Personal Experience and Systematic Review of the Literature - Iacusso, Chiara; Boscarelli, Alessandro; Fusaro, Fabio; Bagolan, Pietro; Morini, Francesco (Frontiers in Pediatrics, 2018)
Introduction: Neonatal gastric perforation (NGP) is a rare entity. Our aim was to report our experience and review the recent Literature to characterize NGP, describe associated factors, and define prognostic factors. Materials and Methods: Retrospective review of all consecutive patients with NGP treated between June 2009 and December 2017 in a third level paediatric hospital. In addition, a systematic review of Medline and Scopus database was performed using a defined strategy. All articles referring to NGP published between 2005 and 2017 were retrieved. Variables considered: prematurity (<37 weeks gestation), birth weight (BW), Apgar score, prenatal complications, age at diagnosis, bag ventilation, pathogenetic events, site of perforation, treatment of perforation, sepsis, and outcome. Mann-Whitney or Fisher’s test were used as appropriate. Results are median (range) or prevalence. Results: Between 2009 and 2016 we treated 8 consecutive patients for NGP and 200 further cases were retrieved from the systematic review (total of 208 patients). Overall survival was 73%. Most frequently eeported pathogenesis: iatrogenic (20 patients), hypoxic/ischemic or infection stress (13 patients), Duodenal/jejunal obstruction (11 patients), drugs (11 patients) esophageal atresia (10 patients). 60% patients had only primary repair of the perforation as gastric surgery. Sepsis developed in 56 patients (34%). Conclusion: Although the pathogenesis of NGP is pleomorphic, prematurity and low birth weight are frequent in these patients. Reviewing our experience and the available Literature, none of the variables considered but sepsis was associated with mortality.